ARCHAEOGENETICS AND HEALTH GEOGRAPHY OF DISEASE IN ASSESSING THE EFFECTS OF PANDEMICS - Syfuddin, Hasan Mahmud (Bangladesh Journal of Multidisciplinary Scientific Research, 2022)
Recent outbreaks of various deadliest diseases provide a histrionic example of the destruction and dread of epidemics, especially those brought on by newly discovered or remerging diseases. Most research on epidemic diseases is dominated by a focus on managing and preventing infections in living populations. Therefore, a systematic study is critically needed to mitigate the risk and impacts of pandemics before it hits globally in an unprecedented manner. In this regard, the historical study of epidemics, alongside the investigation of the health geography, adds temporal depth to our understanding of the causes and effects of diseases essential for making future predictions about how diseases may affect human biology and demography. This review summarizes some of the advancements in our knowledge of the genetic foundations of diseases, recent human changes, and long evolutionary history that can all contribute to understanding how and why people become vulnerable to epidemics. Analyzing the recent COVID-19 pandemic and Cancer data in this review, it has become evident that evolutionary genetics gradually increase our understanding of geographies of disease by combining the knowledge with the evolutionary history recorded in the human genomes. The increasing availability of diverse genetic information from different populations will help us define an individual’s disease risk more precisely in the future. JEL Classification Codes: C22, B15, N3, I12.